Nitric oxide-releasing nanoparticles improve doxorubicin anticancer activity - Alimoradi H (Dove Medical Press, 2018)
Houman Alimoradi,1,* Khaled Greish,2,3,* Anita Barzegar-Fallah,1 Lama Alshaibani,2 Valeria Pittalà4 1Department of Pharmacology and Toxicology, University of Otago, Dunedin, New Zealand; 2College of Medicine and Medical Sciences, Department of Molecular Medicine, and Nanomedicine Unit, Princess Al-Jawhara Centre for Molecular Medicine and Inherited Disorders, Arabian Gulf University, Manama, Kingdom of Bahrain; 3Department of Oncology, Faculty of Medicine, Suez Canal University, Ismailia, Egypt; 4Department of Drug Science, University of Catania, Catania, Italy *These authors contributed equally to this work Purpose: Anticancer drug delivery systems are often limited by hurdles, such as off-target distribution, slow cellular internalization, limited lysosomal escape, and drug resistance. To overcome these limitations, we have developed a stable nitric oxide (NO)-releasing nanoparticle (polystyrene-maleic acid [SMA]-tert-dodecane S-nitrosothiol [tDodSNO]) with the aim of enhancing the anticancer properties of doxorubicin (Dox) and a Dox-loaded nanoparticle (SMA-Dox) carrier. Materials and methods: Effects of SMA-tDodSNO and/or in combination with Dox or SMA-Dox on cell viability, apoptosis, mitochondrial membrane potential, lysosomal membrane permeability, tumor tissue, and tumor growth were studied using in vitro and in vivo model of triple-negative breast cancer (TNBC). In addition, the concentrations of SMA-Dox and Dox in combination with SMA-tDodSNO were measured in cells and tumor tissues. Results: Combination of SMA-tDodSNO and Dox synergistically decreased cell viability and induced apoptosis in 4T1 (TNBC cells). Incubation of 4T1 cells with SMA-tDodSNO (40 µM) significantly enhanced the cellular uptake of SMA-Dox and increased Dox concentration in the cells resulting in a twofold increase (P<0.001). Lysosomal membrane integrity, evaluated by acridine orange (AO) staining, was impaired by 40 µM SMA-tDodSNO (P<0.05 vs control) and when combined with SMA-Dox, this effect was significantly potentiated (P<0.001 vs SMA-Dox). Subcutaneous administration of SMA-tDodSNO (1 mg/kg) to xenografted mice bearing 4T1 cells showed that SMA-tDodSNO alone caused a twofold decrease in the tumor size compared to the control group. SMA-tDodSNO in combination with SMA-Dox resulted in a statistically significant 4.7-fold reduction in the tumor volume (P<0.001 vs control), without causing significant toxicity as monitored through body weight loss. Conclusion: Taken together, these results suggest that SMA-tDodSNO can be used as a successful strategy to increase the efficacy of Dox and SMA-Dox in a model of TNBC. Keywords: biologic barriers, nanoparticles, nitric oxide, doxorubicin, synergistic cytotoxicity, SMA-tDodSNO